Antibacterial and Thermal Insulated Property of Sputtered Copper/Aluminum-Doped Zinc Oxide Films - Shang-Chou Chang; Jian-Syun Wu (Engineering Proceedings)
Recent developments in architectural materials emphasize the importance of antibacterial and thermal insulation functions due to the prevalence of diseases such as COVID-19 and influenza. There is a growing expectation for the implementation of constructed glass that possesses antibacterial properties. Low-emissivity (Low-E) glass, known for its ability to reduce infrared radiation penetration through windows, is a focal point of our ongoing research. In this study, we continued our preliminary investigations into the development of Low-E glass by preparing copper/aluminum-doped zinc oxide (Cu/AZO) films on glass substrates through in-line sputtering. Copper was incorporated to provide antibacterial functionality, while aluminum-doped zinc oxide was chosen for its high visible optical transmission, which is crucial for architectural glass, and its low electrical resistivity indicative of thermal insulation properties. A vacuum annealing process was subsequently applied to the Cu/AZO films on glass. The evaluation of these films involved measuring electrical resistivity that correlates with emissivity, as well as assessing average visible transmission and antibacterial effectiveness according to the JIS Z2801:2000 standard. The results of these tests reveal that the vacuum-annealed Cu/AZO films on glass exhibited commendable antibacterial and thermal insulation properties. Specifically, the antibacterial index (R) was determined to be 8.75; the emissivity, calculated from the measured electrical resistivity, was found to be 0.18; and the average visible transmission was recorded at 52.78%. These findings underscore the potential of Cu/AZO films in advancing the functionality of architectural glass.